Changes in reindeer population numbers in Russia: an effect of the political context or of climate? - Klokov, Konstantin B. (Rangifer, 2013)
This paper analyses trends in domesticated reindeer numbers at the federal, regional, and local levels based on official statistics and interviews with herders in different northern districts across Russia. During the second half of the last century, the domesticated reindeer population in Russia shifted dramatically from a maximum of 2.5 million head to a minimum of 1.2. The most important trends were connected to changes in social and economic conditions linked to government directives. Post-Soviet reforms in the 1990s resulted in a nearly 50% reduction in the total number of domesticated reindeer. However in some regions, these political events had the opposite effect. The contrast was due to the abilities of herders to adapt to the new conditions. A detailed analysis of these adaptations reveals an important difference between reindeer-holding enterprises with common ownership (i.e. kolkhozes, sovkhozes, municipal enterprises, etc.) and households with family owned reindeer. The paper concludes that the effect the political context is so large as to conceal the impact of other natural factors on reindeer populations such as climate change. However, a gradual increase of reindeer populations in the north-eastern part of Russia in the 1960s can be associated with changes in atmospheric circulation patterns.